2016
DOI: 10.3329/bpj.v19i1.29241
|View full text |Cite
|
Sign up to set email alerts
|

Study of Preservatives and Stimulants in Commercial Soft Drinks

Abstract: Commercially available soft drinks i.e., Sprite and 7up (lemon) samples of 10 different batches were studied by UV-Vis spectrophotometry to find out the presence of preservative and stimulant. The wavelength of absorption maxima (max) was 224 nm for sodium benzoate and 272 nm for caffeine. The soft drink samples were degassed, extracted with HPLC grade water and cleaned up to study sodium benzoate and caffeine content. The average quantity of caffeine was in the range of 22 to 30 μg/ml in Sprite and 20 to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These values are lower than what was obtained in our current study. Levels of Sodium benzoate (151.76 -190.04 ppm) higher than the current study have been recorded in a study carried out on Bangladesh soft drinks [22]. Similar studies in India [23] and Srilanka [24] also recorded much higher levels of benzoate than this study; the reported values were 172.35 -396.44 and 33 -631ppm respectively.…”
Section: Resultssupporting
confidence: 62%
“…These values are lower than what was obtained in our current study. Levels of Sodium benzoate (151.76 -190.04 ppm) higher than the current study have been recorded in a study carried out on Bangladesh soft drinks [22]. Similar studies in India [23] and Srilanka [24] also recorded much higher levels of benzoate than this study; the reported values were 172.35 -396.44 and 33 -631ppm respectively.…”
Section: Resultssupporting
confidence: 62%
“…All jelly samples were found to contain sodium benzoate in a range of 160 -289 mg/kg, (approximately 0.16% to 0.28%). The allowable limit of sodium benzoate is 0.1% in jelly 7,8 . Out of 15 jelly samples 10 samples contained yellow 6 in the range of 0.011% to 0.014%.…”
Section: Analysis Of Samplesmentioning
confidence: 99%
“…The use of sodium benzoate as bacteriostatic and fungistatic in soft drinks under acidic condition is very common practice to the beverage companies. However, daily consumption may impact to adverse side effects, such as skin rash, non-immunological contact urticarial, hyperpnoea, metabolic acidosis, and asthma (Sultana et al, 2016). Naturally produced caffeine, a methylxanthine alkaloid found over 63 plant species globally, which is most frequently used worldwide as psychoactive substance (Kapil et al, 2011) in most of the energy drinks due to its stimulating action on central nervous systems (Bispo et al, 2002;Gerald et al, 2014;Pennay et al, 2011;Wanyika et al, 2010).…”
Section: Introductionmentioning
confidence: 99%